A Population-Based Psychometric Validation Study of the Strengths and Difficulties Questionnaire – Hebrew Version - Mansbach-Kleinfeld, Ivonne; Apter, Alan; Farbstein, Ilana; Levine, Stephen Z.; Poznizovsky, Alexander (Frontiers in Psychiatry, 2010)
This study presents the psychometric properties of the Strengths and Difficulties Questionnaire-Hebrew version (SDQ-H), used in the Israel Survey on Mental Health among Adolescents (ISMEHA). The SDQ-H was administered to a representative sample of 611 adolescents and their mothers. Structural validity was evaluated by exploratory and confirmatory factor analysis and the Development and Well-Being Assessment inventory (DAWBA) was used as "gold standard" to test convergent and discriminant validity. Internal consistency and normative scores were established. Agreement was found with the original factor structure, except for the Peer Problem scale. Concurrent and discriminant validity varied from fair to very good for most scales. Total Difficulties scores showed better discriminant validity for the adolescents' than the mothers' report for internalizing disorders, and the opposite for externalizing disorders. Internal consistency for the Total Difficulties was 0.77 and for the Hyperactivity scale it was 0.73. It was lower for the other scales, particularly for the Peer problems scale. The findings suggest reasonable psychometric properties of the SDQ-Hebrew version. Comparisons with other translated SDQ versions are presented.